Efekty dzialalnosci innowacyjnej w przedsiebiorstwach przemyslowych polski wschodniej - Katarzyna Szopik-Depczynska (Institute of Economic Research (IER), 2014)
– The aim of the study was to determine the significance of the use of probit modelling which was a helpful tool to determine the significance of effects to innovative activity, in particular investments in innovations and implementation of new solutions . The main hypothesis of this paper is the claim that the innovative activity of enterprises is dependent on the diversity of factors affecting the parties, and the innovative activity can be influenced in different directions by the effects of this processes. The research was made among 1067 industrial enterprises Western Poland in years 2010-12.
Keywords: O31; L20; R10; 330; innowacyjnosc; przemyl; region